On the presence of a critical detachment angle in gecko spatula peeling - a numerical investigation using an adhesive friction model. Issue 13 (3rd October 2021) - Gouravaraju, Saipraneeth; Sauer, Roger A.; Gautam, Sachin Singh
ABSTRACT: A continuum-based computational contact model is employed to study coupled adhesion and friction in gecko spatulae. Nonlinear finite element analysis is carried out to simulate spatula peeling from a rigid substrate. It is shown that the "frictional adhesion" behavior, until now only observed from seta to toe levels, is also present at the spatula level. It is shown that for sufficiently small spatula pad thickness, the spatula detaches at a constant angle known as the critical detachment angle irrespective of the peeling and shaft angles. The spatula reaches the same energy states at the jump-off contact point, which directly relates to the invariance of the critical detachment angle. This study also reveals that there is an optimum pad thickness associated with the invariance of the critical detachment angle. It is further observed that the sliding of the spatula pad is essential for the invariance of the critical detachment angle. Further, it is found that the invariance of the critical detachment angle is unaffected for a wide range of spatula shaft lengths.